The Effect of Using PQRST on Students' English Reading Skills in Senior High Schools - Farhani, Lutfia Eka; Maulana, Elvandari; Asy’arie, Bima Fandi; Mariyana, Weni; Nuraqilah, Maisarah (El-Syaker : Samarinda International Journal of Language Studies, 2025)
This study examines the effect of using PQRST (Preview, Question, Read, State, Test) on students' reading ability in English narrative texts. The approach used was a quantitative method with a pre-experimental design, involving 34 tenth-grade students at MAN 1 Metro, Lampung, as a sample. Data collection techniques included administering tests, observation, and documentation, while data analysis was conducted through normality tests and normalized hypothesis testing. The results showed a significance value (sig-2-tailed) of 0.000, less than 0.05. Thus, the alternative hypothesis (Ha) was accepted, indicating a significant and positive influence between the independent and dependent variables. These findings suggest that implementing the PQRST strategy can assist English teachers in integrating online and offline learning methods, as this strategy enables students to understand the material effectively both in and outside the school environment.